Electrostatic calibration method for large-amplitude dynamic Casimir force measurements - Cui, Song (2013)
Electrostatic calibration is important in Casimir force measurements. It is necessary for the estimation of the unknown system parameters such as the absolute separation distance and the identification of the electrostatic force model. Correct estimates of the unknown parameters and the electrostatic force model are crucial for interpreting the Casimir force data. In this paper, we present an electrostatic calibration method with higher sensitivity and robustness. It is based on large-amplitude dynamic force measurements. It is proven in theory that the unknown system parameters can be obtained accurately and the electrostatic force model can be identified by our method. The effectiveness and robustness of our method are tested on synthetic data with added noise when the Casimir force measurement is conducted between a sphere and a flat surface.